Perioperative management of cardiac rhythm assist devices in ambulatory surgery and nonoperating room anesthesia. Issue 6 (December 2017) - Arora, Lovkesh; Inampudi, Chakradhari
Abstract : Purpose of review: Patients with cardiac implantable electronic devices (CIEDs) frequently undergo various surgical procedures and in the past perioperative management involved only placing magnet over the device. New programming features, development of implantable cardiac defibrillator (ICD), cardiac resynchronization therapy, and increasing complexity of the operating room equipment have led to new sources of electromagnetic interference (EMI). A comprehensive understanding of the CIED is necessary to provide a timely and optimal care to the patients. Recent findings: Technological advancements and direct implantation of the transvenous implantable cardiac defibrillators into the heart have led to less clear lines between the pacemakers and the ICD. Subcutaneous ICD as well as the leadless transcatheter deployed intracardiac pacemaker development has complicated the issue further. Summary: Rapidly developing technologies and increasing number of patients with these devices coming for noncardiac surgeries necessitate continuous education of the anesthesia team regarding perioperative management of such devices.